Cervantes, literature, and the discourse of politics - Cascardi, Anthony J., 1953- (University of Toronto Press, 2012)
"What is the role of literature in the formation of the state? Anthony J. Cascardi takes up this fundamental question in Cervantes, Literature, and the Discourse of Politics, a comprehensive analysis of the presence of politics in Don Quixote. Cascardi argues that when public speech is constrained, as it was in seventeenth-century Spain, politics must be addressed indirectly, including through comedy, myth, and travellers' tales. Cervantes, Literature, and the Discourse of Politics convincingly reengages the ancient roots of political theory in modern literature by situating Cervantes within a long line of political thinkers. Cascardi notably connects Cervantes' political theory to Plato's, much as the writer's literary criticism has been firmly linked to Aristotle's. He also shows how Cervantes' view of literature provided a compelling alternative to the modern, scientific politics of Machiavelli and Hobbes, highlighting the potential interplay of literature and politics in an ideal state."--Page [i].
Keywords: Cervantes Saavedra, Miguel de, -- 1547-1616. -- Don Quixote.; Cervantes Saavedra, Miguel de, -- 1547-1616 -- Political and social views.; Cervantes Saavedra, Miguel de, -- 1547-1616; Don Quixote (Cervantes Saavedra, Miguel de); Politics and literature -- Spain -- History -- 17th century.; Politique et littérature -- Espagne -- Histoire -- 17e siècle.; LITERARY CRITICISM -- European -- Spanish & Portuguese.; HISTORY -- Renaissance.; Political and social views; Politics and literature; Spain; 1600-1699; History